Architectural character & the history of architecture : the new ladder type curriculum - Salvan, George Salinda (Makati City, Philippines : Goodwill Trading Co, Inc., 2005)
The progress of architecture from the time man settled in one place because of agriculture was slow. He learned the principles of construction by trial and error. There were tools to e invented and manufactured, materials to be acquired and developed.
PART 1: 1. The beginnings of architecture -- 2. Egyptian architecture -- 3. Architecture in the ancient near east -- 4. Pre-columban architecture in America -- 5. Greek architecture -- 6. Roman architecture -- 7. Early christian architecture -- 8. Byzantine architecture -- Islamic architecture -- PART II: 10. Romanesque architecture in Europe, Italy, France, Central Europe, Spain Portugal and the Holy Land, British Isles and Scandinavia -- 11. Gothic architecture in Central Europe, France, British Isles, Spain and Portugal, Netherlands, Late medieval architecture in Italy -- 12. Renaissance architecture in Europe, Italy, France, Spain and Portugal, Britain, German and Central Europe, Russia, Belgium and the Netherlands -- 13. Architecture in Britain -- 14. Architecture in continental Europe -- 15. Architecture of the Americas -- 16. Modern/international architecture -- PART III: 17. Architecture in India and Pakistan -- 18. Architecture in Sri Lanka -- 19. Architecture in Afghanistan, Nepal and Tibet -- 20. Architectura in Burma, Cambodia, Thailand and Indonesia -- 21. Architecture in China -- 22. Architecture in Japan -- 23. Philippine architecture.
Includes bibliographical references and index.
Keywords: ARCHITECTURE HISTORY